Analisis Fenomena Roasting Bercanda dalam Perspektif Hadis pada Mahasiswa Ilmu Hadis Stambuk 22 Universitas Islam Negeri Sumatera Utara - Farhah Nabila Damanik; Sulidar (Kartika: Jurnal Studi Keislaman, 2026)
The phenomenon of joking roasting has increasingly appeared in student interactions as a form of humor, intimacy, and informal social control. However, this phenomenon raises academic concern because not all jokes are received positively, especially when they touch on physical appearance, family background, economic condition, or religion. This study aims to analyze the phenomenon of joking roasting among Hadith Studies students of the 2022 cohort at the Faculty of Ushuluddin and Islamic Studies, Universitas Islam Negeri Sumatera Utara, and to examine the limits of its permissibility and prohibition from the perspective of hadith. This research employed a qualitative method with a case study approach. Data were collected through observation, semi-structured interviews, and documentation, then analyzed descriptively and interpretively by referring to hadiths concerning the prohibition of insulting, guarding the tongue, Muslim brotherhood, and joking ethics. The findings show that roasting is permissible when practiced within close friendships, based on mutual consent, without causing harm or touching sensitive matters. Conversely, roasting that degrades human dignity is considered blameworthy because it contradicts prophetic principles of brotherhood and verbal ethics. This study implies the need to strengthen communication ethics among students so that humor remains within Islamic ethical boundaries